Pengembangan Modul Pendidikan Kewarganegaraan Berbasis Kearifan Lokal di Sekolah Menengah Atas Negeri 1 Kunto Darussalam - Nurjanah Nurjanah; Isnarmi Isnarmi (Universitas Negeri Medan, 2020)
This article aims to develop the learning of Citizenship Education based on local wisdom in improving student learning outcomes on material systems and the dynamics of Pancasila democracy in State Senior High School 1 Kunto Darussalam. The research model used is Research and Development. The focus of the study is in the field of Citizenship Education learning module design which collaborates on the material system and the dynamics of Pancasila democracy with local wisdom of Malay Malay culture. In accordance with Dewey's opinion; learning must be contextualized and adjusted for real life situations (Rusmiati et al, 2013). The data of this study were collected using tests, questionnaires, observations and interviews analyzed qualitatively. From the results of the study showed an increase in the average value of students from 2.1 to 3.1 with a total completeness level of 63.3% to 86.7%. 94.5% of students gave positive responses to learning. From the results of the study concluded that the learning module based on local wisdom can increase students' interest and learning outcomes in the material system and the dynamics of Pancasila democracy.